Comparing the Effects of Long-term Exposure to Extremely Low-frequency Electromagnetic Fields With Different Values on Learning, Memory, Anxiety, and β-amyloid Deposition in Adult Rats - Faraji, Nafiseh; Salehi, Iraj; Alizadeh, Akram; Pourgholaminejad, Arash; Komaki, Alireza; Taheri Azandaryani, Masoumeh; Sadeghian, Reihaneh; Golipoor, Zoleikha (Basic and clinical neuroscience, 2021)
Introduction: Extremely Low-Frequency Electromagnetic Fields (ELF-EMFs) have gathered significant consideration for their possible pathogenicity. However, their effects on the nervous system’s functions were not fully clarified. This study aimed to assay the impact of ELF-EMFs with different intensities on memory, anxiety, antioxidant activity, β-amyloid (Aβ) deposition, and microglia population in rats. Methods: Fifty male adult rats were randomly separated into 5 groups; 4 were exposed to a flux density of 1, 100, 500, and 2000 microtesla (µT), 50 Hz frequency for one h/day for two months, and one group as a control group. The control group was without ELF-EMF stimulation. After 8 weeks, passive avoidance and Elevated Plus Maze (EPM) tests were performed to assess memory formation and anxiety-like behavior, respectively. Total free thiol groups and the index of lipid peroxidation were evaluated. Additionally, for detection of Aβ deposition and stained microglia in the brain, anti-β-amyloid and anti-Iba1 antibodies were used. Results: The step-through latency in the retention test in ELF-EMF exposure groups (100500 & 2000 µT) was significantly greater than the control group (P<0.05). Furthermore, the frequency of the entries into the open arms in ELF-EMF exposure groups (especially 2000 µT) decreased than the control group (P<0.05). No Aβ depositions were detected in the hippocampus of different groups. An increase in microglia numbers in the 100, 500, and 2000 µT groups was observed compared to the control and one µT group. Conclusion: Exposure to ELF-EMF had an anxiogenic effect on rats, promoted memory, and induced oxidative stress. No Aβ depositions were detected in the brain. Moreover, the positive impact of ELF-EMF was observed on the microglia population in the brain.